2020
DOI: 10.1002/jbt.22644
|View full text |Cite
|
Sign up to set email alerts
|

Downregulating lncRNA PRNCR1 ameliorates LPS‐induced pulmonary vascular endothelial cell injury by modulating miR‐330‐5p/TLR4 axis

Abstract: Pulmonary vascular endothelial cell (PVEC) injury following acute lung injury or acute respiratory distress syndrome seriously affects disease development. Recently, accumulating evidence has suggested that long noncoding RNA (lncRNA) exerts significant effects in vascular endothelial cell injury. However, PRNCR1, a novel lncRNA, remains scarcely understood in terms of its functions in PVEC injury. Both in vivo and in vitro models of PVEC injury were constructed by lipopolysaccharide (LPS) administration. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Therefore, PRNCR1 overexpression may promote OA progression by promoting inflammatory responses. Our data and the previous study [ 12 ] suggested that PRNCR1 may play opposite roles in LPS-induced cell apoptosis in different cell types.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Therefore, PRNCR1 overexpression may promote OA progression by promoting inflammatory responses. Our data and the previous study [ 12 ] suggested that PRNCR1 may play opposite roles in LPS-induced cell apoptosis in different cell types.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies of PRNCR1 have mainly focused on its role in cancers [ 25 , 26 ]. A recent study revealed the role of PRNCR1 in increasing pulmonary vascular endothelial cell injury induced by LPS via interacting with miR-330-5p/TLR4 axis [ 12 ]. It has been well-established that LPS-induced inflammation is a critical contributor to the development of OA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biological functions of miR-330-5p are reported to be related with tumor progression, inflammation response, and oxidative stress ( Rambow et al, 2014 ; Feng et al, 2017 ; Xiao et al, 2018 ; Jin et al, 2020 ). Yu et al (2021) reported that the overexpression of miR-330-5p effectively reduced LPS-induced pulmonary vascular endothelial cell injury, and inhibited expressions of TLR4, NF-κB, and inflammatory cytokines. Xing et al (2020) investigated that miR-330-5p overexpression inhibited inflammation and oxidative stress by suppressing the TRAF6/NF-κB signaling in LPS-induced septic cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Sponge function is one of the most important regulatory functions of lncRNAs. It has been found that lncRNAs can sequester microRNAs (miRNAs) to exercise the function of competing endogenous RNAs (ceRNAs) and participate in the regulation of cell proliferation, metastasis, inflammation, autophagy and apoptosis [ 25 ]. However, there are few studies on the involvement of lncRNAs in the regulation of bovine mastitis.…”
Section: Introductionmentioning
confidence: 99%